Influence of animal age on body concentrations of minerals in Japanese quail (Coturnix japonica) - Sales, J; Skřivan, M; Englmaierová, M (Journal of animal physiology and animal nutrition, 2014)
Mathematical modelling of the relationships between mineral inputs and outputs would enable the prediction of mineral requirements of poultry under a wide range of conditions. To establish the feasibility of possible modelling of mineral requirements, the current study aimed to describe the individual mineral concentrations of whole bodies of quail over the life cycle from hatching to 70 days of age. Quail were reared indoors without any restrictions that could limit growth. Sampling of birds (n = 6-18) was carried out at 0, 3, 7, 14, 21, 35, 49 and 70 days after hatching. Freeze-dried samples of whole bodies (digestive contents removed) were analysed for ash, and macrominerals (calcium, magnesium, phosphorus, potassium, sodium) and microminerals (copper, iron, manganese, nickel, selenium, zinc). Ash concentration followed a curvilinear trend, with a maximum of 101.7 g/kg dry matter at 32.77 days. Individual mineral concentrations, expressed as a proportion of ash, were fluctuating over time, with the most prominent changes at 3 days and again at either 14 or 21 days. Dissimilar patterns in individual mineral concentrations resulted that ratios between minerals followed inconsistent patterns over time. Although mineral contents in absolute quantities can be described through modelling over the entire life cycle of the bird, it can be concluded that variable concentrations of individual minerals could complicate further model development.
Keywords: Aging; minerály; Animals; Body Composition; biologické modely; Minerals; Models, Biological; zvířata; složení těla; Coturnix; stárnutí